Pengembangan Lembar Kerja Siswa pada Materi Sistem Persamaan Linear Dua Variabel Berbasis E-Learning - Ari Septian; Mahmud Gustiana (Universitas Sarjanawiyata Tamansiswa, 2022)
This research is a research on the development of teaching materials based on e-learning. This study aims to produce Student Worksheets (LKS) on .-based Two Variable Linear Equation System (SPLDV) material e-learning. The research method used in this research is research and development (R&D) methods. This research is only up to the produce products that are tested for validity and practicality. Study This development adapts the 4D (four-D) development model. This research was conducted through four main stages, namely (1) defining (define) the goal is to find out the initial needs in developing LKS such as, learning objectives and competencies achieved. (2) The design is the stage of making the LKS draft. (3) Development (develop) is a product test that is validated by 7 validator. (4) Dissemination is the distribution of worksheets that have been developed. The results of the LKS validation are: (1) the validator assesses it is feasible with a percentage of (80.31). (2) respondents rated practical with percentage of (77.46). Based on these results, the LKS that has developed feasible and practical to use.